Gadgets as “Kawan Parak”: Exploring YouTube Use, Parental Mediation, and Social Interaction among Children Aged 4-6 Years - Raudatul Hasanah; Khotimatul Majidah S; Muhammad Khairul Ikhsan (AlBanna: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to understand the dynamics of YouTube and digital media use among children aged 4-6 years in Sungai Tandipah Village, Sungai Tabuk District, Banjar Regency, South Kalimantan Province, with a focus on access patterns, parental support, and children's social interactions. The study used a descriptive qualitative approach with an intrinsic case study strategy. Informants consisted of 10 families grouped into three types: families with full-time working parents, families with housewives who use gadgets as a negotiation tool, and families who actively limit screen time. Data were collected through in-depth interviews, passive participant observation, and field notes, then analyzed using thematic analysis. The results showed that gadgets function as “kawan parak” a local term referring to a close companion that accompanies children from morning routines to mealtimes and moments when parents are occupied with work or domestic tasks. However, parental mediation was predominantly passive. Intensive YouTube use was associated with the emergence of “YouTube language,” reduced familiarity with the Banjar mother tongue, emotional outbursts when devices were withdrawn, egocentric behavior, and a shift from traditional play to screen-based peer gatherings. [Penelitian ini bertujuan memahami dinamika penggunaan YouTube dan media digital pada anak usia 4-6 tahun di Desa Sungai Tandipah, Kecamatan Sungai Tabuk, Kabupaten Banjar, Provinsi Kalimantan Selatan,  dengan fokus pada pola akses, pendampingan orang tua, dan interaksi sosial anak. Penelitian menggunakan pendekatan kualitatif deskriptif dengan strategi studi kasus intrinsik. Informan terdiri atas 10 keluarga yang dikelompokkan menjadi tiga tipe, yaitu keluarga dengan orang tua bekerja penuh waktu, keluarga ibu rumah tangga yang menggunakan gadget sebagai alat negosiasi, dan keluarga yang aktif membatasi waktu layar. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif pasif, dan catatan lapangan, kemudian dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa gadget berfungsi sebagai “kawan parak” yang menemani anak sejak pagi, saat makan, dan ketika orang tua bekerja. Pendampingan orang tua cenderung pasif, sehingga anak lebih banyak diarahkan oleh pilihan sendiri dan algoritma YouTube. Penggunaan YouTube berkaitan dengan munculnya bahasa YouTube, gagap bahasa ibu, tantrum, egosentrisme, dan pergeseran permainan tradisional. Penelitian ini menegaskan pentingnya literasi digital keluarga dan pendampingan aktif dalam parenting anak usia dini.]